Prestroke Disability and Outcome After Thrombectomy for Emergent Anterior Circulation Large Vessel Occlusion Stroke. (9th November 2021) - de Havenon, Adam; Castonguay, Alicia; Nogueira, Raul; Nguyen, Thanh N.; English, Joey; Satti, Sudhakar Reddy; Veznedaroglu, Erol; Saver, Jeffrey L.; Mocco, J.; Khatri, Pooja; Mistry, Eva; Zaidat, Osama O.
Abstract : Background and Objectives: To determine the impact of endovascular therapy for large vessel occlusion stroke in patients with vs those without premorbid disability. Methods: We performed a post hoc analysis of the TREVO Stent-Retriever Acute Stroke (TRACK) Registry, which collected data on 634 consecutive patients with stroke treated with the Trevo device as first-line endovascular thrombectomy (EVT) at 23 centers in the United States. We included patients with internal carotid or middle cerebral (M1/M2 segment) artery occlusions, and the study exposure was patient- or caregiver-reported premorbid modified Rank Scale (mRS) score ≥2 (premorbid disability [PD]) vs premorbid mRS score of 0 to 1 (no PD [NPD]). The primary outcome was no accumulated disability, defined as no increase in 90-day mRS score from the patient's premorbid mRS score. Results: Of the 634 patients in TRACK, 407 patients were included in our cohort, of whom 53 (13.0%) had PD. The primary outcome of no accumulated disability was achieved in 37.7% (20 of 53) of patients with PD and 16.7% (59 of 354) of patients with NPD ( p < 0.001), while death occurred in 39.6% (21 of 53) and 14.1% (50 of 354) ( p < 0.001), respectively. The adjusted odds ratio of no accumulated disability for patients with PD was 5.2 (95% confidence interval [CI] 2.4–11.4, p < 0.001) compared to patients with NPD. However, the adjusted odds ratio for death in patients with PD was 2.90 (95% CI 1.38–6.09, p = 0.005). Discussion: In this study of patients with anterior circulation acute ischemic stroke treated with EVT, we found that PD was associated with a higher probability of not accumulating further disability compared to patients with NPD but also with higher probability of death. Classification of Evidence: This study provides Class II evidence that in anterior circulation acute ischemic stroke treated with EVT, patients with PD compared to those without disability were more likely not to accumulate more disability but were more likely to die.